Parents' Knowledge and Commitment To Stimulate Child Development - Fitriyah, Lailatul; Islamiyah, Nurul; Fatahillah, Auliya' (Universitas Nurul Jadid, 2021)
Parents of early childhood need to assert themselves as parents who are ready to oversee the development of their children. In this paper, we will present the results of our research on respondents as parents rather than early childhood, specifically regarding their knowledge and commitment to efforts to stimulate child development. Through the methods of observation, interviews, and filling out questionnaires, we formulated 7 research findings. The 7 findings in question are: 1) PAUD parents mostly live with parents/in-laws, 2) parents of early childhood mostly work as employees and spend most of their day working, 3) parents of early childhood women Small children who work as housewives spend most of the afternoon taking care of the house, 4) PAUD Parents Want Their Children to Develop Well, 5) Early Childhood Parents Want to Stimulate Early Childhood Development, 6) Parents Constraints Obstacles to Early Childhood Opportunities (Free Time) to Stimulate Development, and 7) Early Childhood Parents Limit Knowledge to Stimulate Development. Most of the PAUD parents we met said that they were ready and would try to provide the best education and stimulation for their children's development. However, when faced with difficulties, work, time, and finances, they also appear to be indecisive and think hard. As if true to them, no matter how they try to respond positively, parenting is a difficult and stressful matter.